EU integration and harmonisation of personal income taxation - Tomasz Wołowiec; Janusz Soboń (Contemporary Economics, 2011)
In the process of furthering EU integration little attention was given to the role of income taxes. Multiple income tax systems exist across the Union and their differentiation negatively impacts the European labour market, investments and savings, inhibiting economic growth. Individual nations have little motivation to harmonise as they can engage in tax rate competition and income taxes are interwoven with social security systems that make any attempts at reform extremely complex and politically unpopular. Much of current harmonisation is 'silent', paralegal, and occurs in response to market forces rather than following a formal plan and through intergovernmental cooperation.
Keywords: F15; H20; H24; 330; EU integration; tax harmonisation; personal income taxation; tax system differentiation